Cultural Competence of Secondary School Teachers in Relation to their Self Esteem - Singh, Dr. Richa; Singh, Dr. Seema (Voices of Teachers and Teacher Educators, 2020)
The present study finds the correlation of cultural competence and self-esteem of Secondary School teachers. The sample for the present study consisted of 396 secondary school teachers of Varanasi district selected randomly from the different schools of Varanasi. The tools used for the study were self-constructed Cultural Competence Scale for Secondary School Teachers (CCSSST),Self Esteem Scale by Dr R.N Singh and Dr Ankita Srivastava (Revised Edition 2010) and interview schedule.The results revealed that there is significant correlation between cultural competence and self-esteem of secondary school teachers.Difference were also found in cultural competence and self-esteem of secondary school teachers with respect to mother tongue, family structure, educational qualification, school board and habitat, while no difference were found with respect to gender, religion,& teaching subject.